Ásványtani mozaikok a Kárpát-Pannon régióból 6. - Fehér, Béla; Szakáll, Sándor; Lázár, Károly; Zajzon, Norbert; Bulátkó-DebusDélia; Kristály, Ferenc (Földtani Közlöny, 2025)
Further data are presented on mineral occurrences in the Carpathian–Pannonian region in this sixth instalment of the series arranged by countries and localities. Each “mosaic” contains a concise mineral description, mainly based on XRPD, SEM-EDX and EMPA measurements, and a brief characterisation of the mineral paragenesis. Some minerals are first-time descriptions from the entire discussed region, but all are newly documented occurrences from at least the described locality. From Hungary, mineralogical data are reported on churchite-(Y) from a hydrothermal ore indication in the granite near Pákozd, pumpellyite-(Fe3+) and julgoldite-(Fe3+) from the metabasite of the Darnó Hill in Sirok, and chamosite from manganese concretions in the Jurassic shale of Egerbakta. From Romania, the presence of the following minerals is recorded: reevesite from the serpentinized ultrabasic magmatite of Eibenthal in Banat, axinite from monzodiorite of Groșii Ţibleşului, and braunite from a manganese deposit in the Jurassic sediments of Buceava-Şoimuş. We present the data of evenkite from the fissures of Mesozoic sandstone near Oporets, Ukraine, which was found in calcite fillings in association with hydrocarbon-containing quartz (“Marmarosh diamond” variety).